Gestão da pesca de lagostas do gênero Panulirus no Litoral da Paraíba, Brasil - Oliveira, Patricia Aguiar de (2018)
This thesis was developed with the objective of analyzing the lobster fishery in Paraíba, as well as the socioeconomic profile of the fishermen, in order to contribute to the management of this fishery resource. Aiming at maintaining this extractive and economic activity of coastal communities. This research has the purpose of obtaining a diagnosis of the lobster fishery of the genus Panulirus in Paraíba, to ensure the survival of the resources in parallel with their extraction. The thesis was divided into two chapters that will become articles. The first one is entitled: Mapping of artisanal lobster fishing on the coast of Paraíba and socioeconomic aspects of the fishermen where the fishing ethnography and the lobster fishermen of Paraíba were approached, aiming to build a profile of lobster fishing from of the fisherman's vision, in order to have data that allow to draw up a strategy of fishing, based on the sustainability with focus in the conservation of the fishing resource. A socioeconomic survey of the lobster fishermen of Paraíba was carried out between July/15 and December/17, through interviews based on 40 questions aiming at generating information on artisanal fisherfolk that will help government agencies to outline future support policies, based on local reality. The artisanal fishermen who catch the lobster in Paraíba are mostly adults, aged between 31 and 50 years, married, who have been fishing for more than 30 years, and, depending on the weather, work 3 to 4 days a week. They have an average monthly income of 3 minimum wages, which is usually complemented by extra activities such as construction and others related to fishing. The second chapter deals with the Characterization of the population of lobsters of the genus Panulirus marketed in Paraíba - Brazil, where it was presented results of the quantitative aspects of the population biology of commercialized lobster, as well as the diagnosis of the fishing in Paraíba, which generated a source relevant data for management. The data collected from March 2016 to February 2017 were grouped according to the 6 municipalities in which the survey was conducted. 650 lobsters were sampled. The species with the highest occurrence was Panulirus echinatus (249 individuals). The most frequent recruitment times in winter were identified for the three species. The proportion between the sexes presents a predominance of males in relation to the females for Panulirus argus. Thus, it can be concluded that lobster fishing on the coast of Paraíba is done in an artisanal way, with a poor and dispersed structure, where there is no precise control of its production and is of great importance for part of the fisher population living in the Coast. Some of the problems detected among the interviewees include the reduction of fishing, the invasion of boats from neighboring states, predatory fishing and ineffective inspection by the competent agencies, the lack of infrastructure for processing and the disagreement of the fishing season. closed. All this indicates that the practice of artisanal fishing in Paraíba is not sustainable, it degrades, pollutes, extinguishes, and fishermen are aware of what they do and their consequences. Nevertheless, they continue to repeat this vicious cycle in order to increase the gain, since some have no alternatives.